2016
DOI: 10.2522/ptj.20150427
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapists' Perceptions and Use of Exercise in the Management of Subacromial Shoulder Impingement Syndrome: Focus Group Study

Abstract: Experienced musculoskeletal physical therapists believe that exercise is central in treating patients with SAIS and that gaining patient buy-in to its importance, patient education, promoting self-management, and postural advice are central to the successful treatment of people with SAIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…23,33,34 Experienced therapists note that scapular exercise is a fundamental element in their treatment of patients with shoulder pain likely to have sub-acromial impingement. 35 Another factor that was a positive predictor of overall change in QuickDASH score in the current study was the total number of therapy visits. Though the aim of any treatment protocol is to achieve established goals in as timely a manner as possible, this information suggests there is important value in ultimate patient outcome by persisting with a treatment regimen, even if progress occurs at a slow pace.…”
Section: Comparison To Previous Studiesmentioning
confidence: 64%
See 1 more Smart Citation
“…23,33,34 Experienced therapists note that scapular exercise is a fundamental element in their treatment of patients with shoulder pain likely to have sub-acromial impingement. 35 Another factor that was a positive predictor of overall change in QuickDASH score in the current study was the total number of therapy visits. Though the aim of any treatment protocol is to achieve established goals in as timely a manner as possible, this information suggests there is important value in ultimate patient outcome by persisting with a treatment regimen, even if progress occurs at a slow pace.…”
Section: Comparison To Previous Studiesmentioning
confidence: 64%
“…Given this evidence, therapists should be encouraged to persist in pursuing treatment goals and continue to evaluate specific features of treatment interventions, especially working to see that patient's "buy in" to the value of disciplined compliance with the prescribed exercise regimen. 35 In making this recommendation, it is recognized that beyond some, as yet, unidentified upper threshold of visit number, the positive predictive characteristic indicated by our research probably fades in value. We did not seek to establish that upper limit of visits as that was not the focus of the current study.…”
Section: Comparison To Previous Studiesmentioning
confidence: 72%
“…Individuals with SB are at substantial risk of shoulder muscle weakness, which results in shoulder instability and then causes shoulder pain and dysfunction. Indeed, previous studies have shown that exercise can suppress inflammation (24,25) and improve shoulder function in terms of strength and pain in patients with rotator cuff tears or shoulder impingement (26)(27)(28). Thus, in addition to corticosteroid injection for pain relief, exercise is essential to strengthen the shoulder muscles, maintain the ROM and appropriately prevent the recurrence of SB after corticosteroid injection.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the postural education program was insufficient to achieve shoulder rehabilitation. This is due to the fact that these types of interventions are useful in the prevention of injuries but are ineffective for the recovery of pathologies that are already established [42,43]. Nevertheless, the rehabilitation program based on physical exercise was effective, as it produced adaptations in the soft tissues, which accelerated the recovery process and decreased the perception of pain.…”
Section: Discussionmentioning
confidence: 99%